The Influence of Organizational Culture, Church Management, and Work Motivation on the Performance of GPIB Elders in North Sumatra Province - Izaak Yohannes Bastian Usmany; M. Djoharis Lubis; Saut Purba (Budapest International Research and Critics University, 2022)
This study aims to determine and analyze the influence of: (1) organizational culture on work motivation; (2) church management on work motivation; (3) organizational culture on the performance of elders; (4) church management on the performance of elders and (5) work motivation on the performance of elders. The research subjects were GPIB elders in North Sumatra Province with a sample of 128 people. Sampling with proportionate simple random sampling. The research method is path analysis which aims to test the theory and obtain information about the research. Based on hypothesis testing, it is concluded that there is a direct effect: (1) organizational culture on work motivation is expressed by p31 > r-table (0.492 > 0.159) and t-count > t-table (6.623 > 1.645); (2) church management on work motivation is expressed by p32 > r-table (0.279 > 0.159) and t-count > t-table (3.754 > 1.645); (3) organizational culture on the performance of elders is expressed by p41 > r-table (0.336 > 0.159) and t-count > t-table (4.231 > 1.645); (4) church management on the performance of elders is expressed by p42 > r-table (0.165 > 0.159) and t-count > t-table (2.085 > 1.645) and (5) work motivation on the performance of elders is expressed by p43 > r-table (0.252 > 0.159) and t-count > t-table (2.792 > 1.645). Simultaneously, the results of the study show that organizational culture, church management, and work motivation affect the performance of GPIB elders in North Sumatra Province by 43.2% and the rest is determined by other conditions.